Emerging Technologies in Animal Nutrition and Their Impacts on Sustainability and Productivity: Article Review - Abdullah, Sara Hatem (American Journal of Biology and Natural Sciences, 2025)
This review summarizes the recent progression of new approaches in animal nutrition technology and its application on productivity, welfare, and environmental sustainability. The recent advancements like phytogenic feed additives, probiotics, and prebiotics (i.e., oligosaccharides and galactomannans particularly isolated from guar meal) or multidietary enzymes with complex polysaccharide hydrolysis abilities of NSPs combined with α-glucanase activities towards enhanced utilization potential for the above-said glycoconjugates in monogastric animals, as well as nanobiotechnology tools, are promising ways to achieve precision feeding having better nutrient bioavailability such that there exists overall least dependency upon antibiotic-fed animal health but not at the expense of spoilage to the environment by reducing excreta-emanated deteriorating footprint like GHGs generation, etc. These technologies enable individualized nutrition management, resulting in improved resource efficiency and sustainability. The review also addresses economic and social implications, opportunities, and barriers to adoption. Barriers to adoption are described, and the possibility of future work line recurrence is presented: need for long-term safety studies at different life stages; generalization across environments, breeds, and melding with advanced predictive analytics. Overall, new animal nutrition technologies can contribute significantly to sustainable livestock production worldwide.